Morphological changes in the cephalic salivary glands of females and males of Apis mellifera and Scaptotrigona postica (Hymenoptera, Apidae) - Poiani, Silvana Beani [UNESP]; Da Cruz-Landim, Carminda [UNESP] (Indian Acad Sciences, 2010)
The cephalic salivary glands of some species of bees are exclusive and well developed only in Apinae. These glands were studied with light and scanning electron microscopy in workers, queens and males from the honey bee Apis mellifera, and the stingless bee Scaptotrigona postica in different life phases. The results show that the cephalic salivary glands are present in females of both the species, and in males of S. postica. Nevertheless, they are poorly developed in young males of A. mellifera. In both species, gland growth is progressive from the time of emergence to the oldest age but, in A. mellifera males, the gland degenerates with age. Scanning electron microscopy shows that the secretory units of newly emerged workers are collapsed while in older workers they are turgid. Some pits on the surface of the secretory units correspond to open intercellular spaces. The possible functions of these glands in females and males of both species are discussed.
Keywords: Anatomy; bee; labial gland; queen; scanning electron microscopy; worker